Different Methods of Airway Assessment - El Shamaa, Sara Osman; Ahmed Abaza, Kamelia; Waly, Salwa Hassan; Elsayed, Ashraf Elsayed Ahmed (Journal of Neonatal Surgery, 2025)
Airway assessment is an essential preoperative step that allows prediction of potential difficulties during airway management, particularly tracheal intubation and ventilation. Proper evaluation helps to reduce airway-related complications and improve perioperative safety. Several bedside tests have been proposed to predict difficult intubation, yet their accuracy and reliability remain variable. Comprehensive assessment combining clinical, anatomical, and radiological predictors is therefore vital for safe anesthetic practice.